1999
DOI: 10.1520/jfs12019j
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Seven Methods of Estimating Age at Death from Mature Human Skeletal Remains

Abstract: Different approaches to the estimation of age at death in mature human skeletal remains were evaluated utilizing samples from 19 recent French autopsy individuals of known age at death. Methods of estimating age at death from single-rooted teeth, the sternal ends of the fourth ribs, the symphyseal face of the pubis and femoral cortical remodeling were evaluated by two independent observers (three observers for the teeth). Comparison included ages estimated from three more comprehensive approaches utilizing dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
104
1
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(110 citation statements)
references
References 12 publications
3
104
1
2
Order By: Relevance
“…The dimensions of each pellet were measured using MITUTOYO Digital Callipers to produce a volume measure (V o ). Weights were measured by use of an electronic microbalance (METTER TOLEDO ® College B154) either in air, or in submersion using a liquid of known density (distilled water, density ~1 g/cm 3 ). Samples were first weighed submerged (W sub ) and then in air (wet weight of bone -W w ).…”
Section: P-5mentioning
confidence: 99%
See 1 more Smart Citation
“…The dimensions of each pellet were measured using MITUTOYO Digital Callipers to produce a volume measure (V o ). Weights were measured by use of an electronic microbalance (METTER TOLEDO ® College B154) either in air, or in submersion using a liquid of known density (distilled water, density ~1 g/cm 3 ). Samples were first weighed submerged (W sub ) and then in air (wet weight of bone -W w ).…”
Section: P-5mentioning
confidence: 99%
“…After adulthood, age estimation is based on the assessment of degenerative changes to the symphyseal faces of the pubis and the auricular surface of the ilium; as well as progressive fusion and obliteration of the cranial sutures, the ossification of cartilage at the sternal end of the fourth rib, and the degree of femoral cortical remodelling [3].…”
Section: Introductionmentioning
confidence: 99%
“…3 Age is an important factor, in which there is an increase in bone porosity with increasing age as remodeling results in increased bone resorption and less bone formation. 3 Combined approaches by using both gross and micro-morphological parameters have been used to offer better results, 4,5 including cortical thickness (CT) and histologic parameters. Kerley's method, 6 which requires a complete bone cross section, is widely cited as the most accurate of all histologic methods.…”
Section: Introductionmentioning
confidence: 99%
“…The Suchey-Brooks reference sample is large and includes a number of modern North American ethnic groups. However, despite its popularity, pubic symphyseal age assessment has not performed well in validation studies outside the U.S, including those based on modern French autopsied individuals [20], Canadian pioneers [4], and modern Portuguese and Italian individuals from cemetery collections [10,21]. These studies have demonstrated biased age estimates and difficulty in determining the age of individuals over 35 years.…”
Section: Introductionmentioning
confidence: 99%
“…With the exception of the Buckberry and Chamberlain method that was developed in London, these pubic symphysis and auricular surface methodologies have been developed and tested on modern skeletal samples (samples from later 19 th century to present) derived from North American populations [4,25,27,31,32]. As we have seen before, only a few studies are based on samples outside of the U.S, including India [22], Thailand [2], Great Britain [23], France [20], Italy [10] and Portugal [21]. To supplement this literature, the current study evaluates three methods for adult age estimation using the pubic symphysis [19] and the iliac auricular surface [24,28] …”
Section: Introductionmentioning
confidence: 99%